Ten Year Hepatitis A, B, And C Seroprevalence Trend in Children: Results From A Single Center - YILDIZ, Eren; NARSAT, Mehmet Ali (Medical Records - International Medical Journal, 2022)
Aim: Hepatitis B vaccination since 1998 and hepatitis A vaccination since 2012 is available in the childhood routine vaccination program in Turkey. There is no vaccine for hepatitis C yet. The seroprevalence of hepatitis A, B, and C differs between regions. For this reason, each region should assemble its own rates. Therefore, this study aimed to determine the seroprevalence of hepatitis A, B, and C in children in Kastamonu province, to evaluate whether there is a change in prevalence according to years and patient age, and to review whether there is a change in hepatitis A virus seroprevalence with hepatitis A vaccination. Material and Methods: File records of all patients under 18 whose hepatitis serology was studied at Kastamonu Training and Research Hospital between 01.01.2012 and 21.12.2021 were reviewed retrospectively. Results: A total of 19885 patients and 55738 test results were included in the study. Accordingly, hepatitis A seroprevalence increased year by year. Anti-HAV IgG positivity was higher in the vaccinated group, whereas anti-HAV IgM positivity was higher in the unvaccinated group (p
Keywords: 3. Good health